Pengaruh Terapi Aktivitas Kelompok Stimulasi Persepsi Terhadap Pengetahuan Dan Cara Pelaksanaan Kemampuan Mengontrol Halusinasi Pendengaran Pada Pasien Halusinasi Di Rsud Madani - Rika, Rika; Kadang, Yulta; M, Mariam; utami, Lilik (An Idea Health Journal, 2022)
Auditory hallucinations can be sounds or noises that have no meaning, but are more often heard as a meaningful word or sentence. The voice can be pleasant, telling to do good, but it can also be threatening, mocking, cursing or even frightening and sometimes urging or ordering to do something like kill and destroy. Methods:The design used in this study was a pre-experimental design with one group pre-test-post test. the population in this study were auditory hallucinations patients who were in the salak and sarikaya rooms of Madni Palu Hospital, the sample size was 18 people, the sampling technique was accidental sampling. The results showed that the average value of knowledge before being given group activity therapy (TAK) was 4 .94 and after being given group activity therapy (TAK) the average value became 13.72, which means there was an increase in the average before and after group activity therapy for patients with mental disorders hearing hallucinations. Results: Based on the results of the paired sample t-test (Wilcoxon test) obtained p value 0.000 (p value <0.05), because the p value is smaller than 0.05, thus Ha is accepted and Ho is rejected. Conclusion: It was concluded that Group Activity Therapy (TAK) with perceptual stimulation was very influential in helping patients who experienced a decline in perceptual stimulation with auditory hallucinations.